ANALISIS FRAMING PEMBERITAAN WABAH CORONA VIRUS DISEASE (COVID-19)xDIMEDIAxONLINExOKEZONE.COMxDAN TRIBUNEWS.COMx - muharram fahri (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2022)
The emergence of the COVID-19 virus has become a scourge for society, especially in Indonesia. Various kinds of news about COVID-19 were published in various media, including online media. This study wants to see how the media framing the news of covid 19 in the online media Okezo ne.com and Tribunnews.com. This study uses the framing analysis method of the N. Etman modelwith a descriptive qualitative approach. Data collection techniques were carried out by viewing and observing covid-19 news in the online media Okezone.com and Tribunn ews.com. The overall research results based on the Robert N. Etman framing analysis model with 4 aspects, namely Define Problem, Diagnosis Causes, Make Moral Judgme nt, Treatment Recommendation, stated that the highlighting of the issue of news articles related to covid19 onOkezone .com discussed the impact of covid-19 in several sectors. Meanwhile, Tribunnews.com provides updated information on the development of the Covid-19 case. Tribunnews.com also highlighted the issue of anticipation by the government regarding the handling of COVID-19 ahead of Christmas and the New Year. Keywords: Framing Analysis, News, Covid-19